ICT Based Instructional Design for the Development of Transdisciplinary Learning - Qurrotu Aini; Muhammad Fatchu Reza; Dyah Nur Rahmah; Riris Eka Setiani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the urgency and implementation of Information and Communication Technology (ICT)-based instructional design in the context of transdisciplinary knowledge development. The digital era requires educational approaches that integrate multiple disciplines to produce graduates who are adaptive, innovative, and capable of addressing the complex challenges of the twenty-first century. A transdisciplinary approach, which transcends the boundaries of traditional academic disciplines, is essential for fostering holistic understanding and developing multidimensional solutions to contemporary problems. ICT serves as a key catalyst in facilitating this integration by providing digital collaboration platforms, broad access to knowledge resources, and interactive learning environments. However, the effective implementation of ICT-based instructional design for transdisciplinary learning continues to face challenges, including infrastructure readiness, lecturers' digital competencies, and the development of adaptive curricula. This study employed a qualitative approach using a literature review method to analyze the concept of transdisciplinary education, the role of ICT in supporting its implementation, and the principles of ICT-based instructional design relevant to this approach. The findings indicate that the strategic integration of transdisciplinary learning and ICT can optimize the teaching and learning process, foster creativity, and facilitate collaboration across disciplinary boundaries.